2016
DOI: 10.3747/co.23.2788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Warm Acupuncture on Breast Cancer–Related Chronic Lymphedema: A Randomized Controlled Trial

Abstract: Background Effective treatment for breast cancer-related chronic lymphedema (bcrl) remains a clinical challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 26 publications
0
77
0
Order By: Relevance
“…The basic characteristics of the included studies are shown in Table . A total of 13 randomized clinical trials, comprising 747 participants, were enrolled. The enrolled studies included comparisons of various acupuncture treatments (bloodletting puncturing and cupping, puncture, moxibustion, laser needle and acupuncture) with Western medicine, functional exercise, comprehensive treatment and air‐wave pressure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic characteristics of the included studies are shown in Table . A total of 13 randomized clinical trials, comprising 747 participants, were enrolled. The enrolled studies included comparisons of various acupuncture treatments (bloodletting puncturing and cupping, puncture, moxibustion, laser needle and acupuncture) with Western medicine, functional exercise, comprehensive treatment and air‐wave pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of swelling was used to evaluate the efficacy in 12 studies . Among these, circumference was used in 10 studies, circumference and bioelectrical impedance were used in 1 study, and only bioelectrical impedance was used in 1 study …”
Section: Resultsmentioning
confidence: 99%
“…In addition to improving objective measures of lymphedema at the acupoints, acupuncture appeared to improve quality of life according to the European Organization for Research and Treatment of Cancer’s QLQ-30 questionnaire [59]. Continued study of the optimal regimen of warm acupuncture for treating lymphedema is warranted.…”
Section: Acupuncture/acupressurementioning
confidence: 99%
“…More recently, acupuncture has been used for symptom control in cancer patients. It is helpful in reducing lymphedema, easing nausea and vomiting, and attenuating neurotoxicity in cancer patients [13][14][15][16] . But the evidence of effects on patient quality of life is conflicting 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture has a long history within Traditional Chinese Medicine (tcm) for the successful alleviation of facial neuritis, physical dysfunction, pediatric cerebral palsy, chronic pain, and functional dyspepsia [8][9][10][11][12] . According to tcm theory, acupuncture points have been suggested to have links with specific organs, and stimulation of the acupuncture points could improve organ function and blood circulation, thereby achieving a therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%